If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -20)(x) = 5400 Reorder the terms: (-20 + 2x)(x) = 5400 Reorder the terms for easier multiplication: x(-20 + 2x) = 5400 (-20 * x + 2x * x) = 5400 (-20x + 2x2) = 5400 Solving -20x + 2x2 = 5400 Solving for variable 'x'. Reorder the terms: -5400 + -20x + 2x2 = 5400 + -5400 Combine like terms: 5400 + -5400 = 0 -5400 + -20x + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-2700 + -10x + x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2700 + -10x + x2)' equal to zero and attempt to solve: Simplifying -2700 + -10x + x2 = 0 Solving -2700 + -10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '2700' to each side of the equation. -2700 + -10x + 2700 + x2 = 0 + 2700 Reorder the terms: -2700 + 2700 + -10x + x2 = 0 + 2700 Combine like terms: -2700 + 2700 = 0 0 + -10x + x2 = 0 + 2700 -10x + x2 = 0 + 2700 Combine like terms: 0 + 2700 = 2700 -10x + x2 = 2700 The x term is -10x. Take half its coefficient (-5). Square it (25) and add it to both sides. Add '25' to each side of the equation. -10x + 25 + x2 = 2700 + 25 Reorder the terms: 25 + -10x + x2 = 2700 + 25 Combine like terms: 2700 + 25 = 2725 25 + -10x + x2 = 2725 Factor a perfect square on the left side: (x + -5)(x + -5) = 2725 Calculate the square root of the right side: 52.201532545 Break this problem into two subproblems by setting (x + -5) equal to 52.201532545 and -52.201532545.Subproblem 1
x + -5 = 52.201532545 Simplifying x + -5 = 52.201532545 Reorder the terms: -5 + x = 52.201532545 Solving -5 + x = 52.201532545 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 52.201532545 + 5 Combine like terms: -5 + 5 = 0 0 + x = 52.201532545 + 5 x = 52.201532545 + 5 Combine like terms: 52.201532545 + 5 = 57.201532545 x = 57.201532545 Simplifying x = 57.201532545Subproblem 2
x + -5 = -52.201532545 Simplifying x + -5 = -52.201532545 Reorder the terms: -5 + x = -52.201532545 Solving -5 + x = -52.201532545 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = -52.201532545 + 5 Combine like terms: -5 + 5 = 0 0 + x = -52.201532545 + 5 x = -52.201532545 + 5 Combine like terms: -52.201532545 + 5 = -47.201532545 x = -47.201532545 Simplifying x = -47.201532545Solution
The solution to the problem is based on the solutions from the subproblems. x = {57.201532545, -47.201532545}Solution
x = {57.201532545, -47.201532545}
| c+15=49 | | x-8=-0.35 | | 6^q=q/6 | | 9=9j | | -2x-18=-x-12 | | log(21x)-log(7)=5 | | 19=p-10 | | -0.6y+1.3=4.5-0.2y | | 9x+2=152 | | -3x+11=-2x+6 | | 38=y-39 | | -8=5+s | | 22x-43=14x-17 | | 6x^2+14x-4=0 | | y+42=100 | | 1.6=3y+14.5 | | -7x-3x+2=8-8x-8 | | 12+6w=0 | | 18x-120=10x-72 | | 9999999999999999999999999999999999999999999999999999+99999999999999999999999999999999999999999999999999= | | F(X)=(2x-1)(x+3)(x-2) | | p=50-8x+3x^2 | | 4=52/f | | 15=-7/8(45-X) | | 3z=1.3+2.9 | | f+27=42 | | 3d+5=5-10 | | 4=6+a | | -6n+21= | | r-25=49 | | 5y+12=42 | | 0.09xX=51.29 |